THE INFLUENCE OF SOCIETY 5.0 ON THE SAVI LEARNING MODEL AND STUDENT CHARACTER VALUES ON LEARNING OUTCOMES FOR CLASS VII MTS NEGERI 2 ASAHAN - Farida Suri; Daulat Saragi; Reh Bungana Br Perangin-angin (Sensei International Journal of Education and Linguistic, 2022)
This research was conducted at MTS Negeri 2 Asahan which is located at Jl. Melur No. Ex. Kisaran Naga, Kisaran Timur District, Asahan Regency, North Sumatra postal code 21219. The time of the study was carried out from February 2022 to March 2022. The research method was quasi-experimental. The data analysis technique used is ANOVA. The results of this study are: 1) There are differences in student learning outcomes of class VII MTS Negeri 2 Asahan students who are treated with the SAVI model using video and the SAVI model using power point. It is obtained from Fh = 7.55 and Ft = 4.09, and the conclusion is Fh > Ft. 2) The results of the study where Fh = 22.07 and Ft = 4.09 where the conclusion is Fh > Ft. so it can be concluded that there is an interaction between the SAVI model and the character values of class VII MTS Negeri 2 Asahan students. 3) In this study, the Tukey test was continued, where the conclusion was obtained: there was a significant difference because Q count > Q table. Obtaining Q table = 2 :20 = 2.95 and Qh = 3.76. So it can be concluded that the learning outcomes of students who have high character values taught by the SAVI model and video media are better than students who have high character values taught by the SAVI model and power point media. 4) In this study, the Tukey test was continued, where the conclusion was obtained: there was a significant difference because Q table = 2 : 20 = 2.95. In conclusion, there was a significant difference because Q count > Q table. Obtaining Qh = 9.54.